Is Portuguese population exposed to Zearalenone? A human biomonitoring study as a contribution to the risk assessment of an endocrine disruptor - Martins, Carla (2019)
Zearalenone (ZEN) is a mycotoxin that occurs widely in food commodities with particular incidence in cereals. Due to chemical structures similar to the endogenous oestrogen 17-β-estradiol, ZEN and its metabolites exert estrogenic toxicity. Therefore, it is crucial to assess ZEN exposure among the population and biomarker-driven research is a promising method to assess the human exposure. For this reason, ZEN metabolites such as α-zearalenol (α-ZEL), β-zearalenol (β-ZEL), α-zearalenal (α-ZAL), β-zearalenal (β-ZAL), zearalanone (ZAN) (phase I) and the glucuronides ZEN14GlcA, α-ZEL14GlcA and β-ZEL14Glc (phase II) were identified in biological fluids. With a potency factor of 60 relative to ZEN, α-ZEL is the most relevant metabolite in terms of human health. ZEN is characterized by a fast metabolism and excretion, therefore urine is the matrix commonly used to assess the exposure to this mycotoxin and its metabolites. To date, in Portugal, there is a lack of human studies to assess biomarkers of exposure to ZEN. Within the Scope of National Food, Nutrition, and Physical Activity Survey of the Portuguese General Population (2015-2016), 24h-urine samples and non-consecutive dietary assessments (two 24-hour recalls, 8-15 days apart) from 94 participants were included in the present study. Following a salt-assisted matrix extraction, urine samples were analyzed using LC-MS/MS for the simultaneous determination of ZEN, α-ZEL, β-ZEL, α-ZAL, β-ZAL, ZAN and ZEN14GlcA. ZEN and ZEN-14-GlcA were detected in 52% (36/69) and 14% (10/69) of the analyzed samples, with a mean concentration of 1.2 and 6.9 µg/L, respectively. The metabolites α-ZEL, β-ZEL, α-ZAL, β-ZAL, ZAN were not detected in the urine samples. Considering the 24h-urinary volume, the mean dietary excretion of ZEN and ZEN-14-GlcA was 1.5 and 7.8 µg/day, respectively. These data will allow the determination of Probably Daily Intake of zearalenone with more accuracy since it reflects the internal exposure of participants. The present biomonitoring study generates reliable data regarding the exposure of the Portuguese population to ZEN. These data are crucial to perform a more realistic risk assessment, contributing to the knowledge of determinants of this exposure.